PENGARUH UKURAN PERUSAHAAN, RELATED PARTY TRANSACTION, DAN KOMISARIS INDEPENDEN TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2019-2023 - Nurpadilah, Desti; Rosyati, Tati (UNIVERSITAS DHARMAWANGSA, 2025)
This study aims to determine the effect of Company Size, Related Party Transactions, and Independent Commissioners on Tax Avoidance in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange. The research period is 2019-2023. The type of research used in this study is quantitative with secondary data. The determination of the sample of this study used the purposive sampling method and based on the existing criteria, 29 Company data were obtained and analyzed using panel data regression techniques with a fixed effect model to test the hypothesis. Hypothesis testing in this study used multiple linear regression using Eviews 12. The results of this study indicate that simultaneously Company size, related party transactions, and independent commissioners together have an effect on tax avoidance. The independent variable in the dependent variable is 40.24% while the remaining 59.76% is explained by research other than this study. The results of this study indicate that partially company size has an effect on tax avoidance while related party transactions and independent commissioners have no effect on tax avoidance.